2022
DOI: 10.3390/jcm11123549
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiotherapy: An Alternative Option for Refractory Ventricular Tachycardia to Drug and Ablation Therapy

Abstract: Refractory ventricular tachycardia (VT) often occurs in the context of organic heart disease. It is associated with significantly high mortality and morbidity rates. Antiarrhythmic drugs and catheter ablation represent the two main treatment options for refractory VT, but their use can be associated with inadequate therapeutic responses and procedure-related complications. Stereotactic body radiotherapy (SBRT) is extensively applied in the precision treatment of solid tumors, with excellent therapeutic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, in most cases, cardiac SBRT did not result in complete resolution of VT in long-term follow-up. Therefore, it is currently recommended to use cardiac SBRT in critically ill patients with treatment-resistant (including CA) ventricular tachycardia and electrical storm [68].…”
Section: Management Of Ventricular Arrhythmias In Lung Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most cases, cardiac SBRT did not result in complete resolution of VT in long-term follow-up. Therefore, it is currently recommended to use cardiac SBRT in critically ill patients with treatment-resistant (including CA) ventricular tachycardia and electrical storm [68].…”
Section: Management Of Ventricular Arrhythmias In Lung Cancer Patientsmentioning
confidence: 99%
“…Data on cardiac arrhythmias due to RT are scarce. In a retrospective study, which included 76 LC patients treated from 2010 to 2015 with conventionally fractionated RT, atrial arrhythmias were reported in five patients [68]. The long-term effects of radiotherapy, such as coronary artery disease, cardiomyopathy, valvular heart disease, and heart failure, are much better understood (Supplementary Videos S1 and S2) [4].…”
Section: Radiotherapymentioning
confidence: 99%
“…STAR presents as a highly promising procedure with a major decrease in VT episodes and AAD prescriptions. [7][8][9][10][11][12] The treatment target region in the myocardial wall is subject to cardiorespiratory motion that induces position uncertainties, which makes it challenging to achieve a conformal dose delivery. 13 In addition, adjacent organs at risk (OARs) and cardiac substructures are dose sensitive and the cardiorespiratory motioninduced dosimetric uncertainties raise radiation-induced toxicity concerns.…”
Section: Introductionmentioning
confidence: 99%
“…STAR is applied by delivering a single high‐dose fraction (typically 25 Gy) to the VT isthmus. STAR presents as a highly promising procedure with a major decrease in VT episodes and AAD prescriptions 7–12 …”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic arrhythmia radioablation (STAR) is a specialized procedure that uses advanced imaging techniques to accurately locate and target the areas of the heart arrhytmic substrate responsible for VT [8][9][10]. This technique involves the use of high-energy radiation beams to induce cellular apoptosis and fibrosis also in viable myocardium providing the electrophysiological substrate for VT occurrence.…”
Section: Introductionmentioning
confidence: 99%